Progress without Utopia and Truth - Hofbauer, Reinhard; Wally, Stefan (Momentum Quarterly, 2014)
The history of the term „progress“ is read as a story of de-securing the term. Final aims be they given by god, nature, ideal perfection or truth are disregarded. This de-securing allows for the possibility to see progress as the choice for the better option in real life situations. Even than, there is no „right“ choice, the decision will be developed in collective procedures. Progress is therefore defined not as the new, or the innovation but based on its social character. This criteria is than deployed to refer to indicators of human progress.
Keywords: progress; innovation; politcal theory; growth